Freezing Eggs and Creating Patients: Moral Risks of Commercialized Fertility. (24th November 2017) - Reis, Elizabeth; Reis‐Dennis, Samuel
Abstract: There's no doubt that reproductive technologies can transform lives for the better. Infertile couples and single, lesbian, gay, intersex, and transgender people have the potential to form families in ways that would have been inconceivable years ago. Yet we are concerned about the widespread commercialization of certain egg‐freezing programs, the messages they propagate about motherhood, the way they blur the line between care and experimentation, and the manipulative and exaggerated marketing that stretches the truth and inspires false hope in women of various ages. We argue that although reproductive technology, and egg freezing in particular, promise to improve women's care by offering more choices to achieve pregnancy and childbearing, they actually have the potential to be disempowering. First, commercial motives in the fertility industry distort women's medical deliberations, thereby restricting their autonomy; second, having the option to freeze their eggs can change the meaning of women's reproductive choices in a way that is limiting rather than liberating.